Effect of COVID-19 confinement on the mental status of patients with systemic lupus erythematosus() - Santos-Ruiz, Ana (Med Clin (Engl Ed), 2021)
BACKGROUND AND OBJECTIVE: Patients with systemic lupus erythematosus (SLE) are more vulnerable to higher levels of stress and psychopathological symptoms than the general healthy population. Therefore, the COVID-19 outbreak could alter their psychological state. The objective was to analyze the psychological impact of the pandemic and confinement on stress levels and psychopathological symptoms in patients with SLE. PATIENTS AND METHOD: In this cross-sectional study, stress levels were compared with the Perceived Stress Scale, the Stress Vulnerability Inventory and psychopathological symptoms of the SCL-90-R Symptom Inventory in patients with SLE during the period of confinement (group 1; n = 276) in comparison to patients with SLE evaluated in a period before the pandemic (group 2; n = 152). RESULTS: The comparison between both groups showed there were statistically significant differences in vulnerability to stress (p < 0.0001), depression (p ≤ 0.05), anxiety (p ≤ 0.05), phobic anxiety (p < 0.0001), interpersonal sensitivity (p ≤ 0.043), and psychoticism (p ≤ 0.023). In these variables, the group of patients with lupus in confinement obtained higher scores. CONCLUSIONS: The confinement and threat of the COVID-19 outbreak had important repercussions on the psychological state of patients with SLE with high levels of stress, anxiety, and depression. These findings show their vulnerability to a public health alert and indicate the need to carry out a psychological approach to these patients while the state of health emergency lasts as well as to possible outbreaks of the virus.